2016
DOI: 10.1515/geo-2016-0056
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of development and variability of surface degradation in the subalpine and alpine zones (an example from the Velká Fatra Mts., Slovakia)

Abstract: Abstract:In the last five centuries, the inappropriate management of the Veľká Fatra Mts. sub-alpine and alpine areas has led to the development of different forms of surface destruction. For evaluation of the dynamics and variability of surface degradation the territory of the Hornojelenská valley was chosen. It is a significant avalanche area. It has clearly been destroyed by avalanches, water erosion and cryogenic erosion as well as anthropo-zoogenic processes In the mid-1960s, there were ambitions to refor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Our research has shown a constant expansion of the degraded zone along tourist footpaths in the alpine zone. Similar results were obtained for areas transformed by natural and anthropogenic processes in the subalpine and alpine zones in the Wielka Fatra Range in Slovakia (Lepeška 2016). In addition, work in Bieszczady National Park in Poland has shown a constant expansion of the degraded zone -this despite the use of various reinforcements along tourist footpaths.…”
Section: Footpath Identifiersupporting
confidence: 73%
See 1 more Smart Citation
“…Our research has shown a constant expansion of the degraded zone along tourist footpaths in the alpine zone. Similar results were obtained for areas transformed by natural and anthropogenic processes in the subalpine and alpine zones in the Wielka Fatra Range in Slovakia (Lepeška 2016). In addition, work in Bieszczady National Park in Poland has shown a constant expansion of the degraded zone -this despite the use of various reinforcements along tourist footpaths.…”
Section: Footpath Identifiersupporting
confidence: 73%
“…The very unique characteristics of mountain areas and local determinants, especially bedrock resistance and magnitude of human impact, determine the magnitude of relief change in mountain areas (Leung and Marion 1996;Mihai et al 2009;Monz et al 2010a;Tomczyk 2011;Lepeška 2016;Apollo and Andreychouk 2020; Table 4 Location of analyzed tourist footpath sections and rate of growth of their zones of degradation in the years 1977-2009-2019 (location of footpath sections see Fig. 8).…”
Section: Discussionmentioning
confidence: 99%
“…Trigger zones in the Malá Fatra mountains, which have become the subject of research for several avalanche experts [77][78][79][80] have a slightly higher area (5.1 km 2 ) according to Žiak [56]. The fourth mountain range with an area of trigger zones at 5.2 km 2 is, according to Žiak [56], Vel'ká Fatra, which was subject of avalanche hazards research by several authors [81][82][83][84]. The Ďumbier area of the Low Tatras belongs to the second position in the overall classification of areas threatened by avalanche activity in terms of the extent of trigger zones (11 km 2 ), according to Žiak [56].…”
Section: Discussionmentioning
confidence: 99%
“…While these variables have a comparatively low spatial resolution (30 arcsec, approx. 1 km), they may give a good indication of regional differences in shallow-landslide occurrence as they are representative of alpine processes often linked to the triggering of shallow landslides (Meusburger and Alewell, 2008;Wiegand and Geitner, 2010;Löbmann et al, 2020;Geitner et al, 2021). Specifics on the individual CHELSA variables used can be found in Karger and Zimmermann (2019).…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…precipitation events) and anthropogenic processes (e.g. land-use management) (Tasser et al, 2003;Meusburger and Alewell, 2008;Zweifel et al, 2019;Geitner et al, 2021;Lepeška, 2016). The most visible form of erosion in grassland soils showing bare soil areas can be categorised as shallow erosion (Geitner et al, 2021) (Fig.…”
Section: Introductionmentioning
confidence: 99%